Analisis Pengambilan Keputusan Pemasaran Digital pada UMKM Jasa Kecantikan - Aldi Mulya Pratama; Lucky Prayoga; Rafika Leega Septiadi; Ryan Chritofer; Ujang Suherman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy, particularly in job creation and income distribution. However, the increasingly competitive and digital business environment demands that MSME actors make marketing decisions that are both accurate and adaptive. The shift in consumer behavior toward digital platforms, especially social media, presents both challenges and opportunities for service-based MSMEs. This study aims to identify the marketing decision-making challenges faced by MSME owners, with a case study conducted at Rani Salon in Karawang. Employing a qualitative research methodology, the study utilizes an explanatory survey approach through direct observation and in-depth interviews with the business owner. The findings reveal that the primary constraints in marketing decision-making include limited content ideas, the demands for consistency in digital promotion, and reliance on personal experience in strategy formulation. Nonetheless, decisions to leverage social media platforms such as Instagram and TikTok, and to use WhatsApp Business for communication and reservation, have proven to gradually enhance customer numbers. The discussion indicates that the quality of marketing decisions is significantly influenced by the MSME operators' ability to understand digital consumer behavior and to adjust strategies flexibly. The research concludes that strengthening digital-based marketing decision-making capabilities is a key factor in sustaining and enhancing the competitiveness of MSMEs. The implications of this study are expected to provide practical guidance for MSME practitioners and serve as an academic reference for future research.